Morphosyntactic profiles of Spanish-speaking children with Down Syndrome in a sentence repetition task - Checa-Ponce, Elena; Sebastián, E.; Agüera, E.; Conesa, Macarena; Galeote-Moreno, Miguel Ángel (My University, 2014)
Down Syndrome (DS) is a genetic disorder that is characterized by language delay that is not directly related to the child´s non-verbal cognitive development. Morphology and syntax are the areas that are most affected. The goal of this presentation is to illustrate the morphosyntactic development of Spanish-speaking children with DS by means of a sentence repetition test. Participants were 50 children adolescents with DS compared to 50 typically developing (TD) mental age controls. Mental age (MA) of both groups was between 3 and 5;7 years determined by the Merrill-Palmer scales. Chronological age of the DS group ranged from 3;7 to 18;10 years and for the TD group between 3;3 and 6;7. Groups were matched by sex and MA. Observations were based on a Spanish version of the Devescovi & Caselli (2007) sentence repetition test. It consists of 27 simple phrases (between 3 and 7 words) with different structures and levels of complexity. The test was scored for number of complete sentences produced, MLU and number of omissions and errors (substitutions, additions, etc.) Similar to previous studies in other languages, the children with DS had inferior scores on all measures compared to TD peers. Still, accuracy does increase with age and this suggests that morphosyntactic abilities develop over time in children with DS. Moreover, results highlight that sentence repetition test is an useful measure of linguistic abilities in DS. These results are also discussed compared to the other groups of children presented in the symposium.
Keywords: Lenguaje - Adquisición; Down, Síndrome de; Down syndrome; Morphosyntactic Development